Modelling the impact of emigration upon social and economic development of the Carpathian region of Ukraine - Levytska, Olha; Mulska, Olha; Shushkova, Yulia; Ivaniuk , Ulana; Vasyltsiv, Taras; Krupin, Vitaliy; Ivanova, Liliya (Bulletin of Geography. Socio-economic Series, 2022)
Population migration activity in the Carpathian region of Ukraine is currently high in intensity and scale compared to the national average. This situation is caused by subjective factors (lower living standards and quality of life, employment problems, escalation of armed conflict in the east) and objective factors (globalization and increasing population mobility, development of transnational corporations, digitalization of the economy, simplification of border-crossing procedures). The aim of the research is to model and visualize the impact of population migration on the social and economic development of the Carpathian region of Ukraine and to determine an optimal value and critical range of external migration for the region. Based on the modelling, assuming that socio-economic development of the Carpathian region corresponds to the level of integral coefficient for Poland in 2018 (calculated using a multiplicative approach), the acceptable level of external migration was determined. It is 0.850 for Lviv region (actual migration level was 1.479 in 2018); 0.653 for Chernivtsi region (0.695); and 1.488 for Zakarpattya region (2.149). The critical range of the intensity of external population migration is 0.723–1.264 for Lviv region, 0.499–0.578 for Chernivtsi region, 0.006–0.008 for IvanoFrankivsk region, and 0.479–0.769 for Zakarpattya region.